(untitled) (Fiep Bulletin - online, 2014)
Adopting a healthy lifestyle among the population in general practice regular physical activity can be taken as a challenge for both the institutions and professionals involved in this process .Thus , this study aims to analyze the levels of self-esteem associated with physical activity in college. The research is descriptive, exploratory, comparative, analytical quantitative approach . We used a sample of 110 college students of both sexes , all volunteers from two institutions , one in the city of Rio de Janeiro - RJ , and another in the city of Teresina - PI , aged between 18 and 31 years. To assess self-esteem Scale was used ( Lages , 2012) , which has 16 items considering five dimensions . The results indicated by the Nonparametric Test - Pearson Chi-square - which was performed to analyze differences between groups in concentrations according to sex , with a significance level of p = 0.002 < 0.05 , which indicates there are differences between distributions of the two groups , in which there is a higher frequency of individuals in Group Female Sex do Piauí ( 36/45 ) 80.0 % compared to the Rio Group ( 65/110) 59.1 % . The Student t test indicates there second groups , significant differences between their middle ages , where the Group of Piauí has averaged 21.4 ± 2.7 years significantly lower than that of the Group of Rio de Janeiro who has averaged 31.3 ± 8.6 years. Regarding the classification of self-esteem , the results show a final score as moderate both in group and in the group of Piaui Rio de Janeiro . Therefore , the comparison between the two groups of university denote an average self-esteem associated with moderate physical activity .